1998
DOI: 10.1007/bf03189340
|View full text |Cite
|
Sign up to set email alerts
|

Is one paracetamol suppository of 1000 mg bioequivalent with two suppositories of 500 mg

Abstract: A common belief is that one tablet or suppository containing, e.g. 100 mg of a drug can be substituted, without any changes in the therapeutic effect, with two units of the same brand containing 50 mg of the drug. In the present study a single dose of paracetamol was administered to healthy volunteers as (a) two tablets of 500 mg, (b) two suppositories of 500 mg, and (c) one suppository of 1000 mg. There were statistically significant differences in all bioavailability parameters (t(max), C(max) and AUC) betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…This is suggested by some authors to be the minimum effective antipyretic serum concentration ( 22, 23), although this is not finally proved. A literature survey (Medline search 1966–1999) of pharmacokinetic data published on administration of acetaminophen suppositories showed that after doses of 100–1000 mg acetaminophen maximum concentrations (C max ) of 9.2–86.5 μmol/l were reached 0.4–4.0 h (T max ) after administration ( 1–18). The data from the literature survey are depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is suggested by some authors to be the minimum effective antipyretic serum concentration ( 22, 23), although this is not finally proved. A literature survey (Medline search 1966–1999) of pharmacokinetic data published on administration of acetaminophen suppositories showed that after doses of 100–1000 mg acetaminophen maximum concentrations (C max ) of 9.2–86.5 μmol/l were reached 0.4–4.0 h (T max ) after administration ( 1–18). The data from the literature survey are depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Different authors have demonstrated that the suppository base ( 7, 18, 24), the volume of the suppository ( 13, 17) and the particle size of acetaminophen ranging from 20 μm to 250 μm ( 16, 17, 25) can influence the rate and extent of absorption. Also the number of suppositories administered has been proposed to affect the bioavailability ( 1). The relatively large particle size of the acetaminophen in the suppositories used in our study might have influenced the rate of absorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption from the rectal route of administration is erratic and unpredictable (8,60), with reported values of bioavailability ranging from 24 to 98% (28,59,146,150,190) the mean absorption half-life is 35 min with 40 min lag time (7), but is largely dependent on the physical composition of the suppositories, which varies between manufacturers (60,113), so that the time to peak plasma concentration ranges from 107 to 288 min after rectal administration (9,24,123). In children, an initial rectal dose of 40 mg/kg has been recommended in order to achieve therapeutic plasma concentrations (24); a rectal dose of 45 mg/kg has been reported to produce in children a mean peak plasma concentration of 13 ìg/mL (146), comparable with that obtained with an oral dose of 10-15 mg/kg (188).…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…The rate and extent of dissolution of the rectal suppository is an important factor in determining the degree of absorption and, hence, serum concentration of the drug. [11] The degree of lipophilicity of the vehicle in the suppository, [12,13] the suppository dose size (i.e., smaller dose suppositories dissolve more rapidly than larger sizes), [14] presence of multiple suppositories, [15] pH and temperature within the rectum (influenced by the quantity and consistency of stool in the rectum), and the material that the suppository comes in contact with (stool, bowel mucosa, and other suppositories) are other factors that influence the rate of dissolution, degree of absorption and, hence, the serum concentration achieved by the drug. [16,17] In our study, as there were children aged between 3-12 years with a wide range of body weight, three different suppositories containing different doses of the drug (80, 170, and 250 mg) were combined to deliver the appropriate amount of drug to the children.…”
Section: Group I (Im Pcm) Group Ii (Rectal Pcm) (N = 26) (N = 24)mentioning
confidence: 99%